Governing sea level rise: Evaluating the applicability of China’s coastal adaptation policies to Indonesia - Yasir Arafat; Nur Aini Iswati Hasanah; Affandy Hamid; Puji Setianingsih; Afan Allail Rofikha (Journal of Marine Studies, 2026)
As an Asian-Pacific archipelagic country, Indonesia is increasingly vulnerable to the impacts of sea level rise and coastal hazards. Amid growing risks to infrastructure and water resources, assessing the applicability of coastal adaptation policies from international experience to the Indonesian context is urgent. This paper examines China’s coastal adaptation policies and identifies the critical factors required for their successful adaptation to the Indonesian governance system. A comparative qualitative case study design was employed and guided by the Dolowitz and Marsh policy transfer framework. The analysis systematically evaluates the applicability of three strategic dimensions, i.e., coastal protection strategies, ecosystem-based adaptation initiatives, and the integration of marine spatial planning. The findings indicate that China has implemented these three dimensions through an integrated and systematic governance approach. However, their effective application in Indonesia will depend on overcoming several governance barriers. Critical success factors identified include the necessity for robust intergovernmental coordination, the expansion of fiscal capacity, more stringent enforcement of spatial planning regulations, and the integration of coastal monitoring and data systems. Direct policy replication is unlikely to be effective due to systemic differences between the two countries. Instead, the study advocates for a hybridized approach, characterized by selective adoption and contextual adaptation to Indonesia’s unique institutional and socio-political conditions. This study contributes to the climate governance discourse by providing an empirical bridge between policy transfer theory and adaptation strategies within a comparative Global South setting.